Pengaruh Latihan Small Side Game melalui Interval Method terhadap Peningkatan Kapasitas Anaerobic Alaktasid pada Cabang Olahraga Sepak Bola Kelompok Umur 17 dan 18 Tahun - Khairurrijal, Ramadhani; Imanudin, Iman; Ugelta, Surdiniaty (Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the effect of small-sided game (SSG) training through the interval method on increasing alactasid anaerobic capacity in soccer athletes aged 17-18 years. The research method used is an experiment with a pre-experimental approach. The research subjects were Persib Academy athletes aged 17-18 years as many as 50 people. The results obtained from the initial observation stated that 10 athletes had low anaerobic alactasid levels, so the number of samples used in this study was 10 people and the technique used was purposive sampling. SSG training is applied with variations in intensity and duration, combined with mixed training methods involving anaerobic and aerobic loads. Anaerobic capacity measurements were conducted using the Running-Based Anaerobic Sprint Test (RAST). Data were analyzed by statistical test of inferential analysis with t-test at 5% significant level to determine the significance between variables. The results showed that respondents who underwent SSG training with the interval method experienced a significant increase in alactasid anaerobic capacity. SSG training not only improves physical ability, but provides tactical and technical stimulus relevant to actual game situations.